2014
DOI: 10.1002/jbmr.2341
|View full text |Cite
|
Sign up to set email alerts
|

Lipocalin 2: A New Mechanoresponding Gene Regulating Bone Homeostasis

Abstract: Mechanical loading represents a crucial factor in the regulation of skeletal homeostasis. Its reduction causes loss of bone mass, eventually leading to osteoporosis. In a previous global transcriptome analysis performed in mouse calvarial osteoblasts subjected to simulated microgravity, the most upregulated gene compared to unit gravity condition was Lcn2, encoding the adipokine Lipocalin 2 (LCN2), whose function in bone metabolism is poorly known. To investigate the mechanoresponding properties of LCN2, we ev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
71
3

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 85 publications
(87 citation statements)
references
References 40 publications
13
71
3
Order By: Relevance
“…On the other hand, Guo and co-workers showed opposite results, that is Lcn2 deficiency potentiated diet-induced insulin resistance in mice (Guo et al, 2010). Interestingly, Lcn2 protein level was found to be increased in sera of individuals following bed rest (Rucci et al, 2015), therefore based on our results we may speculate that Lcn2 protein could be at least in part secreted in a soluble form in blood by skeletal muscle tissue similar to the known myokines.…”
Section: Discussionsupporting
confidence: 59%
“…On the other hand, Guo and co-workers showed opposite results, that is Lcn2 deficiency potentiated diet-induced insulin resistance in mice (Guo et al, 2010). Interestingly, Lcn2 protein level was found to be increased in sera of individuals following bed rest (Rucci et al, 2015), therefore based on our results we may speculate that Lcn2 protein could be at least in part secreted in a soluble form in blood by skeletal muscle tissue similar to the known myokines.…”
Section: Discussionsupporting
confidence: 59%
“…F ). Notably, LCN2 is an acute‐phase reactant and antimicrobial peptide that has been shown to play roles in bone development and turnover . To corroborate that elevated LCN2 levels in the serum of MPF mice (Fig.…”
Section: Resultsmentioning
confidence: 93%
“…Using transgenic mice that specifically overexpress LCN2 in osteoblasts, Costa et al reported that LCN2 negatively regulates bone development and formation by affecting growth plate development and attenuating osteoblast differentiation [31]. More recently, Rucci et al identified LCN2 as a novel osteoblast mechanoresponding gene that modulates bone homeostasis [39]. They further demonstrated that in vitro overexpression of LCN2 in primary osteoblasts resulted in reduced expression of Runx2, a master regulator of osteoblasts.…”
Section: Discussionmentioning
confidence: 96%